Peningkatan Kompetensi Guru dalam Melaksanakan Penelitian Tindakan Kelas (PTK) dengan Metode Supervisi Klinis di MTs Negeri 3 Kulon Progo - Munji Jakfar (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
This research aims to improve the competence of teachers in carrying out Class Action Research (PTK) by using the Clinical Supervision (Superklin) method of MTs Negeri 3 Kulon Progo in Semester 2 of the 2021/2022 School Year. The research uses action research methods with two cycles covering planning, action, observation and reflection activities. The results showed that there was an increase in teacher activity in participating in PTK guidance activities in cycle 1 to cycle 2 there was an increase of 16.67%. The results of supervision of teachers in carrying out actions in the classroom in cycle 1 to cycle 2 increased by 33.33%. The results of the assessment of teacher PTK products in cycle 1 to cycle 2 increased by 22.22%. The Superclin method has been empirically proven to improve the competence of teachers in carrying out Class Action Research (PTK) in MTs Negeri 3 Kulon Progo.